EXPLORING ADAPTED SPORTS AND COMPETENCE, RELATEDNESS, AND AUTONOMY IN CHILDREN WITH PHYSICAL DISABILITIES - Bell, Jennifer S. (East Carolina University, 2012)
Self-determination theory states that humans have three basic psychological needs--competence, a feeling of effectiveness or achievement through the completion of a task; relatedness, a sense of belonging or connectedness to others; and autonomy, a perception of being responsible for one's own ideals, actions, and outcomes. The fulfillment of these three needs leads to the psychological growth, wholeness, and well-being of an individual.    The purpose of this study was to examine the relationship between participation patterns in adapted sports and perceived levels of competence, relatedness, and autonomy among children with physical disabilities.   The Basic Psychological Needs Scale, based on Deci and Ryan's Self-determination theory, was given to 37 adapted sports participants, ages 7-18 years old. Results indicated that duration of sport participation was positively correlated with the relatedness construct. There was no correlation between adapted sports participation for competence and autonomy measures. Implications for future programming in adapted sports for children and youth with disabling conditions are provided.
Keywords: Recreation and tourism; Adapted sports; Autonomy; Competency; Physical disability; Relatedness; Sports for children with disabilities; Children with disabilities--Psychology; Quality of life; Self-perception